CRUELTY OF SLAVERY IN AMERICA AS SEEN IN HARRIET BEECHER STOWE’S UNCLE TOM’S CABIN - Apriola, Pipin; Mamentu, Agustine; Kumayas, Tirza (KOMPETENSI, 2022)
The purpose of this research is to examine the cruelty of slavery in America as shown in Harriet Beecher Stowe's Uncle Tom's Cabin. It is done to show the many sorts of enslavement cruelty present in the novel, as well as the causes of the brutality in the story. The writers have decided to undertake this research using qualitative methods. The writers employ a socio-historical method to data analysis. In the discussion is divided into several indicators, such as cruelty of slavery which is divided into slave treat as thing or properties and object of physical violence. The other indicator is slaves suffer as the effect cruelty of slavery which divided into racism, discrimination, slaves’ life is restricted and rebellion. Based on the results of the discussion, it can be concluded that slavery has happened to black people who are very cruel in America and even legalized. South Americans treat black people as slaves inhumanely and treat them like animals.